PEMANFAATAN KACANG MERAH (Phaseolus vulgaris L.) DANJAMUR TIRAM PUTIH (Pleutorus ostreatus) DALAM PEMBUATAN BAKSO NABATI - Khusnul Khuluqiah; Vonny Setiaries Johan; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this research was to obtain the best formulation of red bean and oyster mushroom in making vegetable meatballs. This research used experimental method by using a complete randomized design (RAL) with five treatments and three replication. The treatments were KJ1 = red beans 100% and oyster mushrooms 0%, KJ2 = red beans 90% and oyster mushrooms 10%, KJ3 = red beans 80% and oyster mushrooms 20%, KJ4 = red beans 70% and oyster mushrooms 30%, KJ5 = red beans 60% and oyster mushrooms 40%. Data were statistically analyzed using ANOVA and DNMRT at 5% level. Based on this research the best treatment was meatball KJ4 = red bean 70% and oyster mushroom 30% which had 67.722% moisture content, 2.350% ash content, 0.136% fat content 0.136%, 2.333% crude fiber content. Result of the the sensory test were descriptively colored rather gray, red bean and oyster mushroom taste, red bean and oyster mushroom flavor, and rather chewy in texture. Result of the hedonic test on color, taste, aroma, texture and overall assessment were liked by panelists.